Generations : academic feminists in dialogue - Kaplan, E. Ann; Looser, Devoney, 1967- (University of Minnesota Press, 1997)
Composed of essays from academic women at various professional stages-from established scholars to junior professors to graduate students-this collection illuminates the debates of feminist histories and future legacies, while analyzing the challenges of "passing the torch."